Interactions of Christians and Evangelists of Yazd with Muslims in the Qajar Era - Esfandabadi, Hamidreza Shams; Jadidi, Naser; Boushasb, Feizollah (Journal of History Culture and Art Research, 2017)
The history of Yazd in Qajar era shows several political-social incidents in different periods which have greatly affected the social, cultural, economic and even physical historical-ancient life of the city. Investigating the interaction between Iranians and the residents from different religions during the aforementioned era is interest of the study. This interaction has experienced some fluctuations including peaceful friendships as well as brutal conflicts. The present research is a scientific-investigative effort to perform a historical, periodical, and at the same time documentary and analytical study on the extent, type and method of interactions of the majority of Yazd residents such as Shia Muslims, with the religious minority living in Yazd or non-local Christians temporary living in Yazd for the purpose of performing preaching and advertising programs in Yazd during the Qajar era. The researchers’ hypothesis is as follow: in the Qajar era there was a mutual communication, conflicts and correspondence between Christian minorities (evangelists) and Shia Muslims in Yazd most of which proves a relationship and peaceful co-existence between them. This study applies a comparative-historical methodology as well as examines the academic literature and field studies.